Microfluidic Assisted Self‐Assembly of pH‐Sensitive Low‐Molecular Weight Hydrogelators Close to the Minimum Gelation Concentration. Issue 1 (December 2015) - Hermida‐Merino, Daniel; Trebbin, Martin; Foerster, Stefan; Rodriguez‐Llansola, Francisco; Portale, Giuseppe
Summary: The fibrillation and subsequent gelation of low molecular hydrogelators is usually triggered by external stimuli. Generally, strong acids are employed to trigger the self‐assembly mechanism in pH‐responsive supramolecular systems. However, the generation and design of novel stable gels with performing mechanical properties is a challenging task as a result of the uneven self‐assembled networks formed. Here, we report the study of the self‐assembly process of a low molecular weight hydrogelator (LMWG) in the proximity of its minimum gelation concentration (MGC = 0.3 mg/ml). At such high dilution, the generation of homogeneous gels with good mechanical properties by turning pH by strong acids is a demanding task as a result of the lack of monodisperse 1D self‐assembled rod‐like aggregates. A microfluidic device is employed here to gradually and homogeneously change the pH. We show that self‐assembly of LMWG in well‐defined structures can be enhanced by using the diffusive mixing occurring in the microfluidic reactor channel. For very short mixing times, aggregates with 2 nm cross‐section are found in the region adjacent to the focused LMWG solution in contact with the low pH buffer solution streams, where the pH reaches values below the pKa of the LMWG and triggers the supramolecular self‐assembly. For longer mixing times, aggregates grow in size and occupy homogeneously the micro channel. The results presented here show that better controlled self‐assembly can be achieved using microfluidic mixing devices and early stages of self‐assembly can be efficiently studied by coupling synchrotron SAXS with microfluidics.